The Influence of Performance Allowance Effectiveness on Employee Productivity and Performance with Employee Well-being as a Mediating Variable - Silitonga, Lasmaria; B. Setiadi, Pompong; Dwi, Fanny (SEAN Institute, 2024)
This research investigates the impact of performance allowance effectiveness on employee productivity and performance, considering employee well-being as a mediating variable. Utilizing data processed through SMARTPLS 3.0, the study analyzes direct and indirect effects to evaluate the significance of the relationships. Results indicate that the effectiveness of performance allowances directly influences employee well-being, productivity, and performance. Additionally, employee well-being serves as a mediator, significantly affecting the relationship between performance allowance effectiveness and both productivity and performance. The findings contribute to a comprehensive understanding of the dynamics between performance incentives, employee well-being, and organizational outcomes.